2011
DOI: 10.1021/ja108145c
|View full text |Cite
|
Sign up to set email alerts
|

Size/Shape-Controlled Synthesis of Colloidal CdSe Quantum Disks: Ligand and Temperature Effects

Abstract: Size/shape-controlled colloidal CdSe quantum disks with zinc-blende (cubic) crystal structure were synthesized using air-stable and generic starting materials. The colloidal CdSe quantum disks were approximately square, and their lateral dimensions were varied between 20 and 100 nm with the thickness controlled between 1 and 3 nm, which resulted in sharp and blue-shifted UV-vis and PL peaks due to one-dimensional quantum confinement. The quantum disks were grown with either <001> or <111> direction, polar dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
328
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(351 citation statements)
references
References 53 publications
23
328
0
Order By: Relevance
“…It is known that synthesis of QDs in the presence of anionic X-type ligands, e.g., the benzoate ion, results in surface metal cation rich nanocrystals to maintain the overall charge neutrality of ligand-coated QDs. [44][45][46][47][48][49] We believe that the existence of a similar atomic structure at the surface of our ultrasmall nanocrystals influenced the peak sharpness for 1S(e)-2S3/2(h) transition, as was recently demonstrated for CdSe QDs. 44 The ~8 nm red shift in the broad emission band of our nanocrystals also indicates that their surface was composed of different ligands, which influenced exciton delocalization as will be discussed later.…”
Section: Resultssupporting
confidence: 68%
“…It is known that synthesis of QDs in the presence of anionic X-type ligands, e.g., the benzoate ion, results in surface metal cation rich nanocrystals to maintain the overall charge neutrality of ligand-coated QDs. [44][45][46][47][48][49] We believe that the existence of a similar atomic structure at the surface of our ultrasmall nanocrystals influenced the peak sharpness for 1S(e)-2S3/2(h) transition, as was recently demonstrated for CdSe QDs. 44 The ~8 nm red shift in the broad emission band of our nanocrystals also indicates that their surface was composed of different ligands, which influenced exciton delocalization as will be discussed later.…”
Section: Resultssupporting
confidence: 68%
“…[ 12 ] The quantum disks were synthesized by the reaction between cadmium fatty acid salt and elemental selenium, which is similar to that of CdSe nanoplatelets reported by the Dubertret group. However, the acetate salt, which is the key reagent for the formation of 2D CdSe nanoplatelets, was not needed to obtain the CdSe quantum disks.…”
Section: Cdse Quantum Disksmentioning
confidence: 76%
“…More interestingly, the optical properties of these 2D NCs were very similar to those of CdSe quantum belts reported by the Buhro group, [ 9 ] CdSe nanoplatelets reported by the Dubertret group, [ 10 , 11 ] and CdSe quantum disks reported by the Peng group. [ 12 ] All the 2D CdSe NCs reported so far exhibit very sharp and intense fi rst and second excitonic transitions ( Figure 3 A). The Dubertret group and the Buhro group suggested that the two peaks in [ 11 ] Copyright 2011, American Chemical Society.…”
Section: Optical Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, the CdSe nanocrystal surface was passivated with oleic acid, which bonds to the surface via a carboxylic acid. Previous synthetic work on CdSe nanocrystals has demonstrated that the choice of surface ligands can influence the overall shape of a nanocrystal due to the surface ligands binding more tightly at certain facets [16,26]. It is possible that ligands which bind more tightly to the surface would prevent the surface atoms from rearranging at elevated temperatures; this could lead to nanocrystals of the same size having different melting points based upon their surface passivation.…”
Section: Resultsmentioning
confidence: 99%